Mechanical, Morphological, and Electrical Properties of Polylactic Acid-based Conductive Polymer Composites through Polyethylene Glycol and Carbon Nanotubes Integration - Rifa'i, Awaludin Fitroh; Kaavessina, Mujtahid; Distantina, Sperisa (Periodica polytechnica. Chemical engineering., 2025)
Polylactic acid (PLA) is a biodegradable aliphatic polymer obtained from renewable sources, primarily used in the packaging sector. Electronic components require antistatic packaging to prevent electrostatic discharge (ESD). PLA, being non-conductive, necessitates the addition of conductive carbon nanotube (CNT) to reduce its resistivity and make it suitable for antistatic packaging applications. This research investigates the effect of polyethylene glycol (PEG) on the properties of conductive polymer composites (CPCs) based on PLA, using solvent casting to form film sheets. Four different concentrations of PEG-1,000 and PEG-10,000 (0, 6, 10, and 14 wt%) were utilized to improve the ductility of PLA. CNT was incorporated at a concentration of 8 wt% to enhance the mechanical and electrical properties of PLA. The addition of PEG to the PLA/CNT composites resulted in a reduction in tensile strength while increasing elongation at break, thereby indicating improved flexibility. FTIR analysis revealed significant changes in the carbonyl group peak at 1747 cm−1, with a decrease in carbonyl content observed as the concentration and molecular weight of PEG increased. The electrical conductivity of the CPCs showed a notable increase with the incorporation of 14 wt% PEG, rising from 1.89 × 10−11 S cm−1 to 5.62 × 10−8 S cm−1 (PEG-1,000) and 1.25 × 10−7 S cm−1 (PEG-10,000). These results demonstrate that PEG enhances the mechanical flexibility and electrical conductivity of PLA/CNT composites, making them promising candidates for antistatic packaging applications.